Is Pay an Important Motivator? - Isani, Aalya (2011)
An organisations employee‟s possess skills, knowledge and experience and are therefore of significant value to the organisation. In order to retain theses employees and ensure they perform their best mangers must provide them with motivation. The question of how to motivate employees “has bewildered organisations since the time of wooden ships, when the most popular form of motivation left lash marks” (King and Grace, 2008, p.361). However no such as; pay and fringe benefits or intrinsic motivators such as interesting or challenging work. My research is focused on discovering how Important pay is as a motivator for employees. I chose to conduct qualitative research using a grounded theory approach. My primary data consists of open-ended interviews of eight human resource personnel from various organisations in Pakistan. My research findings suggest that pay is no doubt an important motivator. However managers must consider other factors in the environment as well, such as organisation culture,organisational status, market compatibility and inflation. By focusing on financial incentives alone, managers can lose sight of other areas employees might require assistance in. I hope my research provided valuable insight into motivating employees.